ДОСВІД США У ПРАВОВОМУ РЕГУЛЮВАННІ УНИКНЕННЯ КОНФЛІКТУ ІНТЕРЕСІВ В АДВОКАТСЬКІЙ ДІЯЛЬНОСТІ ТА МОЖЛИВОСТІ ЙОГО ВИКОРИСТАННЯ В УКРАЇНІ - Князева, Наталія Веніамінівна (SUPREMANCE OF LAW, 2017)
The notion of conflict of interests and its influence on the activity of modern advocacy are defined. The legal acts of the United States of America, which regulate the work of lawyers, are analyzed. The most special aspects of legal consolidation of the confl ict of interest phenomenon, possibilities of its avoidance, in the normative system of the USA and ways of using foreign experience in the legislation of Ukraine are singled out.